The art of blending surgical and nonsurgical techniques in aesthetic medicine - Few, Julius (Thieme, 2018)
Innovative strategies for artfully blending aesthetic techniques to maximize results The Art of Combining Surgical and Nonsurgical Techniques in Aesthetic Medicine by Julius W. Few Jr. reflects multidisciplinary contributions from renowned practitioners in plastic surgery, dermatology, oculoplastics, and facial plastic surgery. This is the first book to specifically discuss minimally-invasive aesthetic techniques for the face and body and how to strategically combine them, both with and without surgery. The text is rooted in evidence-based scientific principles and sound clinical applications,